Incidence and Risk Factors of Myocardial Infarction Among Young Adults in a Tertiary Care Hospital in Punjab- A Cross-sectional Study. (Indian Journal of Public Health Research & Development, 2024)
Background: -Cardiovascular diseases, particularly myocardial infarction (MI), are a major global health concern, with a rising incidence among younger populations. MI is a result of inadequate oxygen supply to the heart, often exacerbated by thrombus formation in coronary arteries due to atherosclerotic plaque deposition. Risk factors include obesity, hypertension, dyslipidaemia, diabetes mellitus, smoking, sedentary lifestyle, and familial predisposition. Early detection and intervention are crucial for improving prognosis and reducing mortality rates. Treatment strategies include pharmacotherapy and lifestyle modifications, with lifestyle interventions promoting physical activity and dietary changes. Aim- To determine the incidence and risk factors of Myocardial infarction among young adults. Methodology- This study investigated the prevalence and causes of myocardial infarction (MI) among patients admitted to the Department of Medicine at Adesh Hospital, Bathinda, Punjab. The sample size was 130, with participants being patients aged 18 and above, exhibiting cardiac manifestations, and providing consent for study participation. Data collection involved interactions with MI patients and their relatives, recording demographic information, smoking, and presenting symptoms. Data were analyzed using Microsoft Excel and SPSS version 28, with Chi square used for statistical significance. All data were collected after approval from the Institutional Ethics Committee. Result -The study involved 131 patients diagnosed with Myocardial Infarction (MI) at AIMSR, with 78.6% being males and a mean age of 56 ± 10.8 years. 15.2% of patients were young adults (
Keywords: Myocardial Infarction; Young Adults; hypertension; Cardiovascular diseases